REFUGEE SETTLEMENT IN AUSTRALIA a holistic overview of current research and practice. - Hebbani, Aparna ([S.l.] : ROUTLEDGE, 2024)
Combining theoretical and practical information, this book presents a holistic overview of refugee settlement in Australia. It focuses on numerous critical aspects of refugee settlement which play a vital role in refugee integration into Australia. Starting with an overview of immigration history in Australia, the book then places an emphasis on 21st-century settlement of refugees. The chapters explore a gamut of topics including how culture is transmitted in refugee families, how media portrays refugees, and how to work with refugee communities in various contexts, without focusing on one specific refugee cohort/country group. This interdisciplinary angle is presented via the inclusion of voices from interviews with key refugee settlement providers, educators, former refugees, researchers, and second-generation youth from refugee backgrounds. It covers current Australia political debate and politicisation of refugees, digital technologies, the role of language in enabling successful settlement, education trajectories, social cohesion, the fractured diasporic family, and the impact of media coverage, which underpin the settlement of refugees in Australia. This is an ideal resource for advanced undergraduates, postgraduates, and scholars of refugee settlement in the disciplines of communication, media, politics and international relations, social work, education, and demographic studies, as well as government entities, policy makers, service providers, and NGOs looking to gain an understanding of the factors impacting refugee settlement in Australia.
Keywords: Refugees -- Australia; SOCIAL SCIENCE / Emigration & Immigration; POLITICAL SCIENCE / International Relations / General